Sprejemanje rezultatov študentskih anket o pedagoškem delu med visokošolskimi učitelji in njihov odziv nanje - Pogorelčnik, Tina (Sodobna pedagogika, 2023)
The University of Ljubljana conducts a student evaluation survey to monitor students‘ opinions on individual courses and the teaching performance of higher education teachers and colleagues. The aim is to examine their reception and response to feedback on their teaching performance. The data was collected through a survey questionnaire. 244 teaching staff members at the University of Ljubljana participated in the survey, 15 of whom did not read the student feedback. The final sample consisted of 229 people. The surveyed members of staff generally have a positive attitude towards the feedback. However, their opinion on whether the received feedback should play a major role in promotion decisions is less unanimous. Negative feedback motivates the surveyed teachers to improve their teaching, while positive feedback instils feelings of self-confidence. The received feedback gives most of the surveyed teachers ideas on changes in teaching style and encourages them to improve their teaching. The results show statistically significant differences between teaching assistants on the one hand, and assistant professors, associate professors and professors on the other hand. The most significant difference was in the evoked feelings of confidence when receiving positive feedback and evoked feelings of doubt about one‘s abilities. The findings can offer insight into the reception and response of higher education teachers to feedback. Thus, the conclusions of this thesis can aid the management of the University of Ljubljana in developing strategies for dealing with feedback.
Keywords: feedback; higher education teachers; pedagogical work; pedagoško delo; povratne informacije; student evaluation of teaching; študentske evalvacije poučevanja; University of Ljubljana; Univerza v Ljubljani; visokošolski učitelji